Paradoks: Providensia Allah dengan Penderitaan dan Kematian Manusia - Rolin Ferdilianto Sandelgus Taneo (Program Pascasarjana UKIM, 2023)
The Christian faith offers paradoxes, such as the concepts of Providence and human suffering. Providence is the belief in God's providence as a certainty of faith. However, humans could challenge God's providence because they suffer and even die. This situation puts humans in a dilemma. This article aims to contribute to academic and Christian faith discourse to understand human suffering (death) and God's work in human suffering. Through a study of literature and theological traditions, it was found that the discussion of providence cannot be separated from God's role or work in world history. God works to bring goodness to all His creations. Providence and the experience of suffering seem paradoxical. At the same time, we understand that God cares for us, but at the same time, we cannot deny existential problems, such as death. Death and suffering are realities of life that occur in God's care for His creation.